Emission Inventory of Central Processing Plant in the Oil and Gas Industry in Central Sulawesi - Rasyidi, Achmad Alvinsyah; Syafei, Arie Dipareza; Hermana, Joni; Assomadi, Abdu F. (Devotion : Journal of Research and Community Service, 2024)
The Central Processing Plant (CPP) in Central Sulawesi, Indonesia, is one of the largest oil and gas industries in the world. This study aims to determine the magnitude of the greenhouse gas emission load and identify the operational facilities that produce the highest GHG emissions from CPP Donggi. The study results show an emission inventory for 2021 is 7.609ton CO2-eq per year or 365.78 tonnes of CO2 per TJ in 2021, for 2022 is 8.084ton C2Eq/355.50 tonnes CO2/TJ, and dan for 2023 is 7.565ton. The three highest carbon emission-generating facilities are the Gas Turbine Generator, Acid Gas Removal Unit, and Oil Heater. The research contributes to understanding the scale and distribution of greenhouse gas emissions from a specific industrial source and aids in directing efforts for emission reduction.